Rapid detection of respiratory syncytial virus in community-acquired lower respiratory tract infections in children by chromatographic assay - Surinder Kumar; Bhanu Mehra; Gulshan Rai Sethi; Sanjeev R Saigal (Wolters Kluwer Medknow Publications, 2018)
Respiratory syncytial virus (RSV) is the single most important viral agent causing pediatric lower respiratory tract infections (LRTIs) worldwide. To evaluate the role of RSV in pediatric LRTIs, we studied 85 children <2 years of age hospitalized for community-acquired LRTIs. Nasopharyngeal aspirates were obtained on admission for the detection of RSV antigen by immunochromatographic assay. Demographic, clinical, and radiological findings for RSV antigen were compared. Data analysis was performed by Chi-square test. A relatively higher number of RSV-infected children 32 (60.4%) were below 6 months of age. Clinical and radiological findings in both RSV-positive and RSV-negative groups were comparable. RSV antigen was positive in 53 (62.4%) with immunochromatography. Our study confirms that RSV plays a significant role in community-acquired LRTIs in children.